Board Characteristics and Sustainability Reporting: A Study of Listed Mining Firms in Indonesia - I Gusti Ayu Laksmini Sintia Dewi; Yusli Ayu Laksmini Mariadi (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to examine the influence of board characteristics on sustainability reporting. The research uses a population of mining companies listed on the Indonesia Stock Exchange (IDX) during the period of 2021–2023. A quantitative approach is employed, using content analysis as the research method. Hypothesis testing is conducted using robust standard errors and multiple linear regression with the Year Fixed Effect Model in STATA 17 software. The results of the study indicate that gender diversity has no effect on sustainability reporting. However, the independence of the board of commissioners and the size of the board of directors have a positive and significant effect on sustainability reporting. A limitation of this study is the relatively small sample size, as it focuses solely on mining companies listed on the IDX. Future research is recommended to broaden the scope of companies under study (not limited to the mining sector) and to consider including other board characteristic variables.